(untitled) - Welborn, Ralph (Hoboken, N.J., 2006)
A cutting-edge look at the "DNA of organizational execution" from top business transformation experts Every organization of every size and focus either fails or faces significant frustrations and costs in getting done what it needs to get done. Here, authors Welborn and Kasten argue that there is a simple, fundamental reason why the majority of efforts struggle, if not fail. And understanding this reason-the DNA of execution-makes it possible to manipulate it and thereby "cut through" the complexity of getting stuff done. They illustrate how to make this happen through a broad range of examples, from making strategies more useful, to outsourcing decisions, securing global supply chains, transforming business processes, and integrating existing with emerging technologies. This book presents a big-picture view of getting done what needs to get done that keeps projects coherent and moving forward by helping to decrease risks and increase effectiveness. Ralph Welborn's (Boston, MA) affiliations have included Senior Vice President of Global Solutions at BearingPoint and Managing Partner of Global Business Transformation at Unisys Corporation. He specializes in business transformation, strategic innovation, collaborative and venturing strategies, and global solutions development/deployment.
Keywords: Organizational effectiveness,Industrial management,Tổ chức hiệu quả,Quản trị công nghiệp